1983
DOI: 10.23986/afsci.72123
|View full text |Cite
|
Sign up to set email alerts
|

Variability of topsoil properties at the southern coast of Finland and the number of  soil samples needed for the estimation of soil properties

Abstract: A total of 430 topsoil samples were collected from ten fields of the Viikki Experimental Farm, University of Helsinki. Particle size distribution, organic carbon content, pH(CaCl2), exchangeable Ca, Mg, K contents, plant available P (Bray 1), 1 M KCI extractable (Al+H) content and effective cation exhange capacity of the soils were determined. The coefficient of variation was used as indicator of the variability of soil properties with in each field. The lowest coefficients of variation were observed for pH(Ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
16
0

Year Published

1984
1984
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 3 publications
5
16
0
Order By: Relevance
“…Our findings in Juva and Sotkamo support the current recommendation for soil sampling in Finland of 1−3 samples per hectare (Viljavuuspalvelu 2000). Actually, the number of soil samples should be decided according to the most variable property, which in our fields means four samples per hectare, based on a spatial dependency of 30 m. This is very well in line with the results of Jokinen (1983), who reported that four samples per hectare describe sufficiently the following soil properties: pH, P, K, Mg, Ca, Al, organic C, particle size distribution and cation exchange capacity. In the Juva field, the spatial dependence of B was only 15 m, which is very low and reflects the very rapid changes in the concentrations of B in the field.…”
Section: Discussionsupporting
confidence: 80%
“…Our findings in Juva and Sotkamo support the current recommendation for soil sampling in Finland of 1−3 samples per hectare (Viljavuuspalvelu 2000). Actually, the number of soil samples should be decided according to the most variable property, which in our fields means four samples per hectare, based on a spatial dependency of 30 m. This is very well in line with the results of Jokinen (1983), who reported that four samples per hectare describe sufficiently the following soil properties: pH, P, K, Mg, Ca, Al, organic C, particle size distribution and cation exchange capacity. In the Juva field, the spatial dependence of B was only 15 m, which is very low and reflects the very rapid changes in the concentrations of B in the field.…”
Section: Discussionsupporting
confidence: 80%
“…In an earlier study (Jokinen 1983), the number of soil samples needed for the accurate estimation of soil characteristics was calculated for the topsoil material on the basis of the coefficient of variation (w), Student's t-value (t) and allowable error (p) according to the equation n = t 2w If this equation were applied to subsoils, the number of samples needed would be greater than for topsoil because of the higher w-values in the subsoil. The subsoil seemed to be more heterogenic than the topsoil.…”
Section: Discussionmentioning
confidence: 91%
“…The method of systematic sampling has been reported previously by Jokinen (1983). The present material consisted of topsoil (0-25 cm) and subsoil (30 -50 cm) samples from 382 sampling sites.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Usually one sample composed of 7-8 sub-samples represents 1-2 ha of acreage. The samples were taken from the top-soil in a standardised procedure (see Lakanen 1969, Jokinen 1983, Peltovuori 1999 and analysed according to the routines described by Vuorinen and Mäkitie (1955). Soil sampling was carried out within a five-year period prior to our survey.…”
Section: Soil and Herbage Datamentioning
confidence: 99%